DETEKSI MUTASI GEN Î±-GLOBIN PADA PEMBAWA Î±-THALASSEMIA DENGAN METODE POLYMERASE CHAIN REACTION-SINGLE STRAND CONFORMATION POLYMORPHISM (PCR-SSCP) - , ISKANDAR, Dr. Niken Satuti Nur Handayani, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Seventeen samples of total 98 whole blood samples from hematological test which conducted by Yayasan Thalassemia Indonesia/Persatuan Orangtua Penyandang Thalassemia Indonesia (YTI/POPTI) Yogyakarta in cooperation with Laboratorium Klinik Prodia and Faculty of Biology UGM were suspected of Î±-thalassemia carriers. The objective of this study was to determine whether subjects that suspected were carrying the mutant gene South East Asian deletion (SEA deletion) and to detect the polymorphism that occurs in Î±-globin gene. The method was conducted by extracting DNA from blood samples using the Genomic DNA Mini Kit (Blood/Cultured Cell) Frozen Blood Protocol, Î±-globin gene amplification, electrophoresis, and Polyacrylamide Gel Electrophoresis (PAGE). Data analysis was performed using qualitative analysis that is based on presence the pattern of DNA ribbon in PCR and PCR-SSCP results. The results showed that PCR was carried out successfully and the mutant fragment (195 bp) was obtained, as well as the normal fragment (314 bp). While the results of PCR-SSCP was showed that 17 samples were heterozygous of Î±Â°-thalassemia carriers. It can be concluded that, the studied subject were carrying the mutant gene SEA deletion on Î±-globin gene and the polymorphism that occur on Î±-globin gene is heterozygous of Î±Â°-thalassemia carriers or Î±-thalassemia type 1 with two genes deletion.